Narrowband radar system for indoor doorway detection - Liu, Yunxiang (2015)
Radar is an object-detection system that uses radio waves to determine the range and direction of objects. It could be employed on an Unmanned Ground Vehicle (UGV) for autonomous navigation. Although the UGV could sense the surrounding environment by using optical sensors such as camera or infrared sensors, these sensors may not work well in some environments, such as an environment with low visibility or an environment with obstacles made of transparent or polished materials. In these cases, radar sensors could be employed along with these optical sensors to enhance the navigation capability of an UGV.